2006
DOI: 10.1029/2005jg000071
|View full text |Cite
|
Sign up to set email alerts
|

Ramifications of increased salinity in tidal freshwater sediments: Geochemistry and microbial pathways of organic matter mineralization

Abstract: [1] The effects of salinity intrusion on the anaerobic microbial and geochemical dynamics of tidal freshwater sediments were investigated using flow-through sediment reactors. In freshwater control sediments, organic matter mineralization was dominated by methanogenesis (62%), followed by sulfate reduction (18%), denitrification (10%), and iron reduction (10%). Upon salinity intrusion, nutrient (ammonium, silicate, phosphate) concentrations increased and rates of methanogenesis declined. Iron-oxide bioavailabi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

22
201
3

Year Published

2009
2009
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 234 publications
(230 citation statements)
references
References 64 publications
22
201
3
Order By: Relevance
“…Among studies that have manipulated the TEA pathway through substrate amendments, some report greater rates of carbon mineralization in the presence of NO 3 À compared to methanogenesis (Pallud et al, 2007;Abell et al, 2009) or SO 4 2À compared to methanogenesis (Reddy and Graetz, 1988;Weston et al, 2006;Pallud et al, 2007). However, in a comparison of 10 different wetland soils, D'Angelo and Reddy (1999) did not observe a difference in organic carbon mineralization rates under denitrifying, sulfate-reducing or methanogenic conditions.…”
Section: Introductionmentioning
confidence: 70%
See 3 more Smart Citations
“…Among studies that have manipulated the TEA pathway through substrate amendments, some report greater rates of carbon mineralization in the presence of NO 3 À compared to methanogenesis (Pallud et al, 2007;Abell et al, 2009) or SO 4 2À compared to methanogenesis (Reddy and Graetz, 1988;Weston et al, 2006;Pallud et al, 2007). However, in a comparison of 10 different wetland soils, D'Angelo and Reddy (1999) did not observe a difference in organic carbon mineralization rates under denitrifying, sulfate-reducing or methanogenic conditions.…”
Section: Introductionmentioning
confidence: 70%
“…Yet, other studies suggest that the free energy yield of TEAs does influence mineralization rates in anaerobic environments. Weston et al (2006) reported that a shift from methanogenesis to sulfate reduction in flow-through reactors loaded with tidal freshwater river sediment doubled mineralization rates. Using flow-through reactors and intertidal marsh sediments, Pallud et al (2007) found that nitrate reduction led to faster rates of organic matter decomposition versus sulfate reduction.…”
Section: Role Of Electron Acceptorsmentioning
confidence: 99%
See 2 more Smart Citations
“…For example, between 1998 and 1999, elevated CO 2 stimulated CH 4 emissions in the C 3 -dominated community by 0.2-0.4 g C m -2 year -1 compared to a stimulation of CO 2 emissions by 34-393 g C m -2 year -1 over the same time period (Marsh et al 2005). Low rates of CH 4 production in this brackish system are likely the result of sulfate inputs from seawater driving the competitively dominant process of sulfate reduction (Kelley et al 1990;Megonigal et al 2004;Weston et al 2006b). Our data show that CH 4 concentrations were generally low in both treatments in the C 3 -and C 4 -dominated plant communities until SO 4 2-concentrations were depleted (Fig.…”
Section: Anaerobic Heterotrophic Metabolismmentioning
confidence: 99%